1973
DOI: 10.1073/pnas.70.12.3735
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Orientation of Cyclic AMP-Dependent Protein Kinase in Human Erythrocyte Membranes

Abstract: The topographic location of cyclic AMPdependent protein kinase has been studied in preparations of permeable and sealed membranes derived from human erythrocytes. Both the catalytic and cyclic AMP-binding components of protein kinase are localized on the inner, cytoplasmic, surface of the plasma membrane.3':5'-Cyclic AMP has been implicated in the regulation of a variety of membrane-associated functions including: contact inhibition (1, 2), hormone secretion (3), cellular permeability (4), and synaptic transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The enzyme appears to reside exclusively at the cytoplasmic side of the membrane (106), a further argument for the presence of the phosphorylated proteins at that surface. Whether the cyclic AMP binding site, which has also been ascribed to the inner surface of the erythrocyte membrane (106,139), is the same as the regulatory site of the protein kinase is uncertain, since the cyclic AMP concentration required for half-maximal saturation of the binding site (3 nM) is 10 100 times lower than that required for half-maximal stimulation of phosphorylation (135,136,139). Photoaffinity labeling was recently used to demonstrate that the 50,000-dalton polypeptide whose phosphorylation is most stimulated by cyclic AMP probably corresponds to this cyclic AMP binding site (140).…”
Section: P H O S P H O R Y L a T I O N Smentioning
confidence: 99%
“…The enzyme appears to reside exclusively at the cytoplasmic side of the membrane (106), a further argument for the presence of the phosphorylated proteins at that surface. Whether the cyclic AMP binding site, which has also been ascribed to the inner surface of the erythrocyte membrane (106,139), is the same as the regulatory site of the protein kinase is uncertain, since the cyclic AMP concentration required for half-maximal saturation of the binding site (3 nM) is 10 100 times lower than that required for half-maximal stimulation of phosphorylation (135,136,139). Photoaffinity labeling was recently used to demonstrate that the 50,000-dalton polypeptide whose phosphorylation is most stimulated by cyclic AMP probably corresponds to this cyclic AMP binding site (140).…”
Section: P H O S P H O R Y L a T I O N Smentioning
confidence: 99%
“…Labeling is not stimulated by cyclic AMP (adenosine monophosphate) in vitro. The phosphate appears to be introduced only from the cytoplasmic surface [77] . Drickamer [50, 511 has found that phosphorylation occurs primarily within 10,000 daltons of the cytoplasmic N terminus of band 3, but that some 32Pi can also be detected in fragments ascribed to the center of the polypeptide chain.…”
Section: Phosphorylatio Nmentioning
confidence: 99%
“…This behavior has recently been demonstrated with respect t o the major sialoglycoprotein (17). Component a migrates as a wide band at an apparent molecular (18). Carbohydrates have been repeatedly demonstrated on the outer surface available to the external environment of the erythrocyte (19)(20)(21).…”
Section: Discussionmentioning
confidence: 91%